The influence of Youtube beauty vloggers on Indonesian Muslim consumers purchase intention of halal cosmetic products - Mita Elvira (NUsantara Islamic Economic Journal, 2022)
This study aims to analyze and explain the influence of YouTube beauty vloggers on Indonesian Muslim Consumer’s Purchase Intention of Halal Cosmetic Products. This study uses a data collection method with a questionnaire, with a quantitative approach. The population that is the object of research is muslim women in Tanjungpinang. The study sample numbered 100 respondents using purposive sampling techniques with convenience sampling approach. The criteria of respondents are muslim women aged 17-35 years who are domiciled in Tanjungpinang and use halal cosmetics. The analytical tool used in this study is SPSS 26. The results of this study show that YouTube beauty vloggers are very influential on purchase intentions with a coefficient of determination of 63.6%. With the YouTube beauty vloggers are able to influence consumer behavior and increase consumer confidence and able to increase purchase intentions on halal cosmetic products. It can be concluded that YouTube beauty vloggers have a positive and significant effect on purchase intentions.